Golden Berry (Physalis peruviana) Juice for Reduction of Blood Glucose and Amelioration of Insulin Resistance in Diabetic Rats - Kinasih, Larasati Sekar; Djamiatun, Kis; Al-Baarri, Ahmad Ni’matullah (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2020)
The study aimed to gather evidence on the potential of golden berry (GB) juice in improving blood glucose level, insulin level, and insulin resistance in type-2 diabetes mellitus (T2DM) in comparison to quercetin supplement in animal model. This study used true experimental pre-post-test study with control group design. Twenty five Wistar male rats were divided into five groups: healthy group (K-), T2DM positive control group (K+), T2DM group with 1 ml/200 g BW/day of GB juice (X1), T2DM group with 5 ml/200 g BW/day of GB juice (X2), and T2DM group with 6 mg/200 g BW/day of quercetin (X3). The T2DM rasts were obtained from healthy rats induced by high-fat feed and Streptozotocin (STZ). The result showed that various dosages of GB juice (X1 and X2) were able to lower blood glucose level (-79.15; -110.44; -108.20) and HOMA-IR (-2.40; -2.92; -3.02). In addition, it was also able to increase insulin level (0.26; 1.99; 1.42) compared to (K+) group (p<0.05). In conclusion, GB juice was able to lower blood glucose level, insulin resistance, and increase insulin level in T2DM rats. The GB juice dosage of 1 ml/200 g BW/day and 5 ml/200 g BW/day were better in lowering the blood glucose level and improving insulin resistance compared to quercetin supplement.